The application of Islamic Law in a Muslim Minority Community: an examination of Sri Lankan Muslim scholars’ opinions from the perspective of Maqāṣid al-Sharīʽah - Shihan, Mohammad; Zaroum, AbdulHamid Mohamed Ali; Amanullah, Muhammad (Department of Fiqh and Usul al-Fiqh, IIUM, 2022)
Presently, Muslims face many challenges and problems due to the changes in space, time, culture, and modern developments. The various contemporary issues are more related to Islamic law compared to ʽAqÊdah and morality. Accordingly, Islamic Sharīʽah is increasingly becoming the central discourse among academicians since it is the way of life for Muslims irrespective of time and space. Nonetheless, prevailing narrow understanding about Sharīʽah, rather than broad, is problematic. Furthermore, this situation is more crucial in a Muslim minority context than in a Muslim majority territory. This leads to many misunderstandings and misinterpretations among Muslims and non-Muslims about Sharīʽah. Therefore, the application of Sharīʽah has become a controversial matter that harms people’s interests rather than serves them. At the same time, during the last few decades, there is significant interest among the students and scholars of Sharīʽah in proclaiming the Maqāṣid al-Sharīʽah as a new methodology to interpret the texts of Sharīʽah. They propose Maqāṣid al-Sharīʽah as general principles that open expansive rooms for applying Sharīʽah under its broad perspective. Acknowledging this background, the researchers examined the views of Sri Lankan Muslim scholars about the application of Sharīʽah based on Maqāṣid al-SharÊÑah’s viewpoint. Hence, the perceptions about the application of Sharīʽah are collected from selected Muslim scholars by conducting interviews. This study follows the qualitative method of data collection and content analysis method to reach the results and findings. Hence, the study uses primary and secondary sources such as books and journal articles and direct interviews with local scholars. Accordingly, the study reveals that the prevailing narrow perspective about Sharīʽah made the Sri Lankan Muslim community find the application of Sharīʽah impossible. Because the understanding of Sharīʽah is limited mainly to branches and rules of Sharīʽah within the realms of individuals and family, communal matters have been paid less attention. Consequently, the study concludes that the broad perspective of Sharīʽah opens a wider space for the application of Sharīʽah and helps Muslim minorities realize their rights and further extend their contributions to others. At the same time, this approach paves the ways for cooperation and collaboration with other religious communities.